2010
DOI: 10.1186/1743-422x-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing and non-neutralizing monoclonal antibodies against dengue virus E protein derived from a naturally infected patient

Abstract: BackgroundAntibodies produced in response to infection with any of the four serotypes of dengue virus generally provide homotypic immunity. However, prior infection or circulating maternal antibodies can also mediate a non-protective antibody response that can enhance the course of disease in a subsequent heterotypic infection. Naturally occurring human monoclonal antibodies can help us understand the protective and pathogenic roles of the humoral immune system in dengue virus infection.ResultsEpstein-Barr Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 31 publications
5
87
0
Order By: Relevance
“…50 Likewise, other studies that detected neutralizing antibodies in primary and secondary infections observed that, in the presence of an infection caused by serotype 1, the serotypes with the highest antibody titers corresponded to serotypes 1 and 3. 13,51,52 The multitypic response was positively associated with age because of the diversity of antibodies generated as a result of ongoing exposure in addition to triggering an increase in the titer against the others as a result of a cross-reaction response.…”
Section: Discussionmentioning
confidence: 99%
“…50 Likewise, other studies that detected neutralizing antibodies in primary and secondary infections observed that, in the presence of an infection caused by serotype 1, the serotypes with the highest antibody titers corresponded to serotypes 1 and 3. 13,51,52 The multitypic response was positively associated with age because of the diversity of antibodies generated as a result of ongoing exposure in addition to triggering an increase in the titer against the others as a result of a cross-reaction response.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses were propagated in LLC-MK 2 as previously described (30). LLC-MK 2 cells were inoculated with DENV stock at 70% to 80% confluence and cultured in DMEM and 10% (vol/vol) FBS.…”
Section: Methodsmentioning
confidence: 99%
“…In the work of Schieffelin et al, three antibodies that targeted the E protein were isolated from a single donor (30). All three antibodies were cross-reactive with at least two DENV serotypes, one was neutralizing, and all were able to enhance DENV infection.…”
mentioning
confidence: 99%
“…Previous reports described the specificity of MBCs isolated several weeks after acute infection with a known dengue serotype, followed by clone immortalization using EBV, screening of the secreted Abs, and cloning of Ab genes (13)(14)(15)(16). Most Abs isolated in this way were found to react with conserved epitopes in the prM and E domain of the virus or with nonstructural proteins and, therefore, were largely serotype cross-reactive.…”
mentioning
confidence: 99%